2014
DOI: 10.4103/0019-5154.143575
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous angiosarcoma of head and neck

Abstract: Cutaneous angiosarcoma is a rare aggressive tumor of capillary and lymphatic endothelial cell origin. Cutaneous angiosarcoma of the head and neck regions seems to be a distinctive neoplasm with characteristic clinicopathologic features that differ from angiosarcoma in other anatomic locations. Angiosarcoma, regardless of their setting, has a bad prognosis. We presented here a case of 80 years old male, with multiple nontender grouped purple to red hemorrhagic vesicular and bullous lesions over left lower cheek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…1,2,3,7 Current treatment modalities include complete surgical resection, radiation therapy and chemotherapy. 2,4,5 Chemotherapy is recommended for metastatic disease, and chemotherapeutic agents that have shown activity against angiosarcoma include anthracyclines and taxanes. 2,5 However, cutaneous angiosarcoma of the head and neck can present with multifocal lesions, indistinct borders and extensive skin involvement due to clinically undetectable intradermal spread.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,3,7 Current treatment modalities include complete surgical resection, radiation therapy and chemotherapy. 2,4,5 Chemotherapy is recommended for metastatic disease, and chemotherapeutic agents that have shown activity against angiosarcoma include anthracyclines and taxanes. 2,5 However, cutaneous angiosarcoma of the head and neck can present with multifocal lesions, indistinct borders and extensive skin involvement due to clinically undetectable intradermal spread.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Studies have shown that only half of patients survive over 15–18 months. 1 , 4 Prognostic factors include tumor size greater than 5 cm in diameter, depth of invasion, margin status, recurrence and metastases. 1 , 2 , 3 , 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in clinical presentation and the lack of disease awareness contribute to the difficulty in diagnosis 3 ; however, early detection and intervention is critical for improved prognosis. The size of lesion at presentation is an important prognostic factor for cutaneous angiosarcoma 3 , and a delayed diagnosis may lead to substantial challenges in treatment 4 . Perez et al reported that a tumor size less than 5cm was associated with a significantly improved overall and recurrence-free survival compared to a tumor size greater than 5cm 5 .…”
mentioning
confidence: 99%
“…It mainly occurs in fair skinned males (sex ratio of 3:1), at an average age ranging from 60 to 80 years. [1] Very few Indian case reports, mostly males, have been documented till date.…”
mentioning
confidence: 99%